Peran Komunikasi Hexahelix Dalam Konstruksi Sosial Mitigasi Covid-19 Pada Masyarakat Badui Luar - Made Wilantara; Misnan Misnan (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
The purpose of the study was to find out the social construction of the reality of the Badui community against zero percent COVID-19 transmission. The research approach is qualitative with a constructivist paradigm. The research method is descriptive with purposive data collection. The results showed that the Bureaucrats (Local Government Officials) carried out effective externalization-internalization communication management, namely instructions from the central government could be implemented maximally with effective coordination of meaning. Furthermore, the Customary Head carries out legitimacy–socialization communication management, which emphasizes that COVID-19 must be overcome by treating ancestral heritage and following government instructions in interacting. Next, Scholars (Badui Culture Observers) carry out institutionalization-objectivation communication management, namely that the community must obey the rules and customary culture and believe in the Almighty. As for the Volunteers, they carry out socialization communication management, namely providing input and warnings to the local community to maintain the health of their respective families. Other supports are health workers, through health communication and the communication nodes of the Badui community themselves as small circles at the family and community level (internalization).